PEMAHAMAN PELESTARIAN ALAM WARGA PINTUBESI DI KAB DELISERDANG - Lukgimin Aziz; Nurliani Siregar; Elirani Gea; Hasahatan Hutahaean (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Conservation of nature, maintaining the balance of the ecosystem is an inseparable part of the divine mandate of God. Preserving nature and the balance of ecosystems means that we have done part of the faith. Community service by providing education on nature conservation is carried out to give residents a better understanding. The activity was carried out by selecting a group of residents in Pintubesi, especially Hindus. This implementation is based on the location of Pintubesi hamlet, Laurakit village in Deliserdang district, around (surrounded) nature with green forests. The life of the majority of residents is not farming, and a small number of broiler breeders. Therefore, to support nature conservation and maintain ecosystems, it is necessary to provide understanding to the residents there. The implementation of the activity uses the extension method by preparing materials and some practical materials during the extension. Meanwhile, residents were selected from a Hindu community to provide concentration and focus on counseling and monitoring after the counseling. From several counseling sessions, pleasant results were obtained regarding the understanding and awareness of participants in preserving nature and the role of humans in maintaining the balance of the ecosystem. Participants enthusiastically participated in each counseling session and arrived on time. Awareness and responsibility for conserving the surrounding nature are united by maintaining one's own farmland. Preserving and maintaining nature has been asked to become a lifestyle.